Biofortification of calcium on mustard (Brassica juncea L.) and lettuce (Lactuca sativa) cultivated in floating hydroponic system - Fitra Gustiar; Munandar Munandar; Sekar Wahyu Ningsih; Muhammad Ammar (Buletin Agroteknologi, 2020)
Calcium (Ca) is one of the essential macrominerals needed by the human body as a major component in the formation of bones and teeth. Calcium is fulfilled by eating calcium-rich foods, both animal and vegetable. Mustard and lettuce are vegetables that can be a source of Ca. Efforts to increase the Ca content in plants can be done through increasing the concentration of Ca given through fertilizer or in nutrient solution. However, excessive Ca application is not recommended because it will be toxic to plants. This study aims to determine the effect of various Ca concentrations in hydroponic nutrient solutions on the growth and yield of mustard vegetables (Brassica juncea L) and lettuce (Lactuca sativa L.). This study used a floating hydroponic system with a completely randomized design. Treatment of Ca concentrations of hydroponic nutrient solutions that were tried were 0, 100, 200, 300, and 400 ppm. The parameters observed were plant height, number of leaves, level of greenness of leaves, fresh and dry weight, and concentration of calcium in the leaves. The results showed that Ca treatment significantly affected the number of leaves and the level of leaf greenness. Application of 400 ppm Ca in hydroponic nutrient solution is the highest Ca concentration that could increase Ca content in mustard and lettuce plants. Application of Ca 300 ppm is the highest concentration of hydroponic nutrient solution that can increase the Ca content of plants without causing a decrease in plant biomass, and therefore the treatment of Ca 300 ppm can be used for biofortification of Ca by hydroponic in mustard and lettuce plants.